Efficacy and safety of subcutaneous semaglutide in adults with overweight or obese: a subgroup meta-analysis of randomized controlled trials - Zhang, Rui; Hou, Qin-chuan; Li, Bing-hong; Deng, Ling; Yang, Yu-mei; Li, Ting-xin; Yao, Xiao-qin; Yang, Liang-liang; Lin, Xi-long; Liao, Yi-qian; Wang, Lin; Liu, Yu-ping; et al. (Frontiers in Endocrinology, 2023)
Background Semaglutide shows significant performance on weight reduction in several clinical trials. However, it is not clear what kind of administration frequency or dosage will achieve better effects. This study aims to explore the different therapeutic effect of semaglutide on weight control under the diverse administration circumstances. Methods The PubMed, Embase, Web of Science, Cochrane Library, and the ClinicalTrials.gov were searched from inception until 6 June, 2022 to include randomized controlled trials evaluating the Efficacy and safety of subcutaneous semaglutide in overweight or obese adults. Random effects or fixed effects model was conducted based on the heterogeneity among trials. Subgroup analysis was performed to identify the detailed effects under different intervention situations. Findings Our study included 13 RCTs involving 5,838 participants with 3,794 ones in semaglutide group and 2,044 in placebo group. Semaglutide was associated with a significant reduction on weight loss related outcomes, including the absolute value of weight loss (WMD -8·97, 95% CI -10·73 to -7·21), percentage of weight loss (WMD -10·00, 95% CI -11·99 to -8·00), body mass index (WMD -3·19, 95% CI -4·02 to -2·37) and waist circumference (WMD -7·21,95% CI -8·87 to -5·56). Subgroup analyses illustrated participants with high weekly dosage, long-term treatment duration and severe baseline BMI (Class II obesity) had a more remarkably decreasing on the main outcomes of weight loss (P for interaction<0·05). Total adverse reactions occurred more frequently in the daily administration group than that in the weekly group (P for interaction=0·01). During the treatment, the incidence rate of hypoglycemia was higher in the group without lifestyle intervention compared with that with lifestyle intervention (P for interaction=0·04). Interpretation Subcutaneous semaglutide had significant benefits on weight loss with reasonable safety in overweight or obese adults. Moreover, additional benefits on cardiometabolic profiles were also seen. We recommended semaglutide treatment to be coupled with lifestyle interventions, and target dose of 2·0 mg or more subcutaneously once weekly. Clinicians can choose suitable treatment schemes based on diverse individual situations.